"Really Social Photojournalism" and a Photojournalistic Changing of the Guard: Observations and Insights. Issue 4 (2nd October 2017) - Tait, Gabriel B.
Abstract : In a changing technological ecosystem where photojournalists are attempting to reach larger audiences, they are forced to serve multiple masters and social media platforms. The tools and terminologies that these visual storytellers and communicators are using are also changing, which forces many of them to grapple with their roles and how best to contribute their craft within a market that is drastically different than two decades ago. This study asked 104 photojournalism practitioners, academicians, and administrators to define and explain the term "Really Social Photojournalism" and if it might rise past the level of jargon in a changing vocation? The findings reveal there are many complexities with this new term. But there are also opportunities for RSP to evolve in the photojournalism ecosystems with the appropriate support of its various stakeholders.